MOLLUSCA DIVERSITY IN PAMEUNGPEUK BEACH, SOUTH OF GARUT, WEST JAVA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2022)
Mollusk in intertidal zone have a unique way for self-defend and have different spesies biodiversity than other zones. So we need to learn in-depth of the diversity and ways of their adaptation. The aim of this study were to determine the spesies and diversity of mollusk, to observe the adaptation and the economic benefits of mollusk, and determine of mollusk cluster community. This research were located in Pameungpeuk, Garut, West Java included Bubujung, Karang Paranje, Santolo Indah, Karang Papak, Taman Manalusu, Cicalobak, Karang Wangi, Ranca Buaya 2 and Ranca Buaya 1 Beach. The observation found 37 species of mollusks consist of 33 species gastropoda and 4 species bivalvia. Mollusks adapt by hiding in rocks and looking for moist areas to maintain water levels in their bodies. Species with a high number of individuals and distribution were Nodilittorina, Trochoides, and Littorinidae. The highest diversity index (H’) of mollusk is found in Ranca Buaya 1 (H’ 2.8) and the higest index of evenness (e) is found in Parenje beach (0.92). The mollusks that have potential economic to be developed in Pamengpeuk beach included Planaxis sulcata, Nerita polita, Nerita picea, Cerithium eburneum, and Turbo setosus. Pemengpeuk Beach has a high level of diversity and distribution of mollusks so that it potential to be developed in order to improve the sustainability and economy of the people in that region.